The Propagation of Misinformation in Social Media A Cross-platform Analysis - Rogers, Richard (Amsterdam University Press, 2023)
There is growing awareness about how social media circulate extreme viewpoints and turn up the temperature of public debate. Posts that exhibit agitation garner disproportionate engagement. Within this clamour, fringe sources and viewpoints are mainstreaming, and mainstream media are marginalized. This book takes up the mainstreaming of the fringe and the marginalization of the mainstream. In a cross-platform analysis of Google Web Search, Facebook, YouTube, Reddit, Twitter, Instagram, 4chan and TikTok, we found that hyperpartisan web operators, alternative influencers and ambivalent commentators are in ascendency. The book can be read as a form of platform criticism. It puts on display the current state of information online, noting how social media platforms have taken on the mantle of accidental authorities, privileging their own on-platform performers and at the same time adjudicating between claims of what is considered acceptable discourse.